ACCESSIBILITY AND UTILIZATION OF PUBLIC HEALTHCARE FACILITIES: AN INVESTIGATIVE STUDY OF PRIMARY HEALTH CENTRES IN NAMAKKAL DISTRICT, TAMIL NADU - Karthigaiselvam, A.; Ramasamy, Dr.S. (International Journal of Psychosocial Rehabilitation, 2020)
In the Demand - Supply nexus effective utilization of healthcare services provided by the state government hospitals, PHCs, HSCs and District Head Quarters hospitals assumes a greater significance as those who use are mostly from weaker sections of the society. Hence, the issues of accessibility and utilization of such healthcare facilities assumes importance. A field study conducted in villages coming under three upgraded PHCs in Namakkal District, TamilNadu state covered 281 patients. It was found that most of the cases were treated in maternity and child healthcare wards. Another group of out-patients took treatment for both communicable and non- communicable diseases. In the case of physical accessibility, people from 35 Km radius are using the services and reach the PHCs through government buses. Out of three upgraded PHCs (Namagiripet, Pillanallur and OlapattiSowdapuram) selected in Namakkal district, O.Sowdapuram is not having sufficient transport facilities for the people to reach the PHC and rest two PHCs have adequate transport facilities.The healthcare facilities at the Namagiripet Upgraded PHC are relatively better with special care units like Dental, Radiographer, Blood Bank, Operation Theatre and a DGO specialist doctor. However, these kinds of facilities were missing in Pillanallur and O.Sowdapuram PHCs. The selected patients demanded that the healthcare infrastructure has not been adequate and quality of healthcare services has also to be improved.